Bosworth-type fibular entrapment fracture of the ankle without dislocation: a rare case report and a review of the literature - Han, Sang-Jin (Ann Transl Med, 2021)
Bosworth fracture-dislocation of ankle is a rare and irreducible type of ankle injury, with a high incidence of complication. This type of fracture was defined originally as entrapment of the proximal fragment of the fibula behind the posterior tubercle of the distal tibia. Recently, many variants of this type of fracture dislocation have been reported, but all of those reports included the syndesmosis ligament injury of ankle. Here, we report a case of a particularly rare variant of Bosworth fracture-dislocation without syndesmosis ligament injury of ankle. A 48-year-old male presented with a Bosworth fracture dislocation with entrapment of proximal fragment behind the tibia. After temporary treatment in emergency department was applied, emergency open reduction and internal fixation with a plate and screws was performed due to irreducibility of the fracture fragment. The fractured lateral malleolus was entrapped behind the tibia and rupture of the interosseous ligament was found intraoperatively. The anterior inferior tibiofibular ligament, a part of syndesmosis ligament of ankle, was grossly intact and no abnormal findings was seen by fluoroscopy with external rotational stress. Moreover, the deltoid ligament was found to be normal in ultrasonography. There were no complications after surgery and the patient showed full functional recovery at 2 years follow up. These fractures will frequently be irreducible and should be considered for open reduction and internal fixation with the careful evaluation of injury mechanisms with syndesmotic stability.